POST-PANDEMIC ECONOMIC RECOVERY IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW ON KEY DRIVERS, CHALLENGES, AND POLICY IMPLICATIONS - Sulis Yunita Ulani; Rozzy Aprirachman (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
PURPOSE - The COVID-19 pandemic has profoundly disrupted Indonesia’s economy, exacerbating structural vulnerabilities and necessitating targeted recovery strategies. This study conducts a systematic literature review (SLR) to synthesize empirical and theoretical insights on the key drivers, challenges, and policy implications of Indonesia’s post-pandemic economic recovery.METHODOLOGY - By analyzing 45 peer-reviewed articles, government reports, and international organization publications (2020–2023), this research identifies critical drivers such as digital transformation, government stimulus programs, resilience of micro, small, and medium enterprises (MSMEs), and increased foreign investment. However, persistent challenges—including labor market imbalances, regional disparities, inflationary pressures, and global economic uncertainty—hinder equitable recovery.FINDING - The findings underscore the need for adaptive, inclusive policies that balance immediate economic stabilization with forward-looking reforms. This study contributes a comprehensive framework for policymakers to navigate post-pandemic recovery complexities, emphasizing integrated strategies to strengthen Indonesia’s economic foundation against future crises.